Evaluation of The Factors Affecting Voluntary Participation in Sports Events in Turkey: Case of Vodafone 39th Istanbul Marathon - Hamza Uslu; Musa Çon; Mehmet Yalçın Taşmektepligil; Taner Tunç; Aydan Ermiş (Selcuk University, 2020)
The purpose of this article is to determine the factors that influence the motivations of the 39th Istanbul Marathon volunteers towards this event. This study was conducted on a total of 196 volunteers, 95 male and 101 female. Information about the participants was provided by Sport Events Volunteer Motivation Scale (SEVMS). For the statistical evaluation of the study, first factor analysis was conducted in order to determine whether the SEVMS provided a basic pattern of the scale and reliability analysis was conducted to determine whether it was measuring a holistic structure. Since Bartlett's test for sphericity Chi-square value was 2582.64 (p lt;0.05) and Kaiser-Meyer-Olkin value was 0.849 as a result of the reliability and factor analyses, it was concluded with factor analysis that the items could create patterns at high levels. According to the results of the study, it was found that in terms of the students' departments, there were statistically significant differences in purposive, solidary and external traditions sub-dimensions and volunteer motivation total scores in favour of sport students and graduates. Therefore, it should be ensured that the success of the organization is increased by providing the individuals who have received or who are receiving education in the field of sport to participate in sports events. In addition to this, efforts should be made so that the students who are studying in the field of sport can experience the subjects they study in school. Another important result of the study is that external traditions sub-dimension scores of volunteers who have low English level are higher when compared with volunteers who have moderate and high levels of English. This is because international sport events provide volunteers a chance to improve foreign language skills. In this regard, volunteers who have low foreign language levels should be appointed with foreign language-knowing volunteers and their expectations should be met and they should be given opportunities to become global citizens in the globalizing world.